The Impact of Puberty Timing on Future Metabolic and Hormonal Disorder Risk - Buliszak, Agnieszka; Babczyńska, Monika; Marcjasz, Piotr; Bioły , Anna; Dryja, Patryk; Boczar, Agata; Chodkowska, Ewa; Bielas, Kinga (Quality in Sport, 2025)
Introduction and Objectives: Puberty is occurring earlier across populations, raising concerns about long-term health effects. Early onset—marked by younger age at menarche in girls or early voice change in boys—has been linked to adverse metabolic outcomes, including type 2 diabetes mellitus (T2DM) [1]. This review explores how pubertal timing influences the risk of metabolic and hormonal disorders, focusing on T2DM. Brief Literature Review: Earlier puberty correlates with higher risks of obesity, insulin resistance, and T2DM [1]. Each one-year delay in menarche reduces T2DM risk by 9%, independent of adult adiposity [2]. Girls with menarche ≤11 years and boys with early voice breaking show elevated T2DM odds [2]. Early puberty is also associated with higher adult BMI, gestational diabetes, and PCOS [1,13]. Mechanisms include childhood obesity, insulin resistance during puberty, and hormonal shifts [14]. Some effects persist beyond body weight influences [5,6]. Conclusions: Early puberty is a marker—and possibly a mediator—of increased T2DM and hormonal disorder risk [1,2]. Pubertal timing may independently impact long-term health. Identifying at-risk youth could support early interventions. Further research should explore causal pathways and prevention strategies.